Psychological Profile of Patients with Myocardial Infarction: from Risk Group to Rehabilitation - A. S. Elzesser; R. V. Kadyrov; T. V. Kapustina (Вестник Кемеровского государственного университета, 2022)
High morbidity and mortality make cardiovascular diseases socially significant. The Health Development Strategy of the Russian Federation though 2025 states the importance of diagnosis, treatment, and prevention of cardiovascular diseases. This research featured the psychological profile of patients with myocardial infarction at different stages: 1) risk of myocardial infarction, 2) soon after myocardial infarction, 3) after rehabilitation. The study involved 159 patients aged 38–47, including those at risk (43), those soon after a heart attack (39), those after rehabilitation (37), and a conditionally healthy control group (40). The psychological characteristics were assessed using a number of psychodiagnostic methods and included cognitive, emotional, and behavioral components of personality. The obtained data were processed using the nonparametric Mann-Whitney U-test (significance level=0.05) and calculated with STATISTICA 10.0. The research revealed active early maladaptive schemes. At all stages, the patients experienced a contradictory combination of the need for approval and intransigence in relation to other people's mistakes, high anxiety and irritability, non-constructive strategies for coping with stress, and a low level of reflexivity. These factors were interconnected, caused destructive behavior, and increased the psycho-emotional stress. The research also covered the attitude to the past, present, and future at different stages of disease development. The trends revealed the effect of psychological profile on behavioral factors that could increase the risk of primary and recurrent myocardial infarction. The results can help specialists to improve the existing psychological support programs for cardiovascular patients, develop preventive measures for risk groups, and identify targets for psychotherapeutic work with these two categories.